The Nativity (San Diego : Voyager Books/Harcourt Brace & Comp, 1986)
Illustrates the story of the birth of Jesus and the arrival of the wise men and shepherds at the manger.
Text consist of excerpts from the authorized King James version of the Bible.
Keywords: Jesus Christ-Nativity-Juvenile literature; Jesus Christ-Nativity; Bible. N. T. Luke